Traumatic partial amputation of the tongue. Case report and literature review - Hernández-Méndez, José Roberto (Ann Med Surg (Lond), 2015)
INTRODUCTION: The traumatic injuries to the tongue can go form section to partial or complete amputation, the latter being a rare presentation in the setting of facial trauma or even in patients with mental illness. CASE REPORT: We present 25-year-old patient with traumatic partial amputation of the tongue who presented to the emergency department with successful surgical repair with good functional and esthetic outcome. DISCUSSION: The tongue can suffer a broad type of traumatic injuries, in the setting of active bleeding, the muscular planes must be closed with absorbable sutures to stop the hemorrhage and prevent hematoma formation. Tongue surgical repair in the setting of a total section requires integrity of arterial and venous flow, so anastomosis must be executed. CONCLUSION: Amputation of the tongue can put the patient's life at risk and its management needs to be mastered by the surgeons treating polytraumatized patients.